2017
DOI: 10.1515/tjb-2017-0087
|View full text |Cite
|
Sign up to set email alerts
|

Determination of petroleum biodegradation by bacteria isolated from drilling fluid, waste mud pit and crude oil

Abstract: Objective:In this study, the aim was to isolate and identify bacterial strains in crude oil, drilling fluid and waste mud pit samples collected from the same oil field, determine the petroleum biodegradation and find the most effective bacteria in the samples in petroleum biodegradation.Methods:The contents of crude oil, drilling fluid and waste mud pit samples were enriched in appropriate conditions. Upon identification of the isolated bacteria, the incubations in petroleum containing media were performed at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 21 publications
1
14
1
Order By: Relevance
“…The highest petrol degradation efficiency (69.5% ± 13.44 / 6 days) was observed for IUBP15. While highest petrol removal efficiency reported in the literature is 30% per seven days for Bacillus tequilensis grown in the presence of crude oil (1% v/v) for seven days at 30°C (Ozyurek and Bilkay 2017). In the present study, the lowest petrol degradation rate (41% ± 32.6 / 4 days) was noticed for IUBP1.…”
Section: Discussioncontrasting
confidence: 53%
See 3 more Smart Citations
“…The highest petrol degradation efficiency (69.5% ± 13.44 / 6 days) was observed for IUBP15. While highest petrol removal efficiency reported in the literature is 30% per seven days for Bacillus tequilensis grown in the presence of crude oil (1% v/v) for seven days at 30°C (Ozyurek and Bilkay 2017). In the present study, the lowest petrol degradation rate (41% ± 32.6 / 4 days) was noticed for IUBP1.…”
Section: Discussioncontrasting
confidence: 53%
“…This is parallel with the earliest studies in which petroleum hydrocarbons metabolizing bacteria like Bacillus cereus, Proteus mirabilis, Bacillus subtilis, Enterococcus faecalis, Streptomyces sp. ERI-CPDA-1, Bacillus mojavensis ATHE13 and Bacillus licheniformis ATHE9 have been reported (Balachandran et al 2012;Eskandari et al 2017;Ozyurek and Bilkay 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All these features of fungi make them unique for industrial usage derivatives (1,3). Although the biodegradation of petroleum hydrocarbons with different bacterial strains, bacterial consortia and fungal strains have been investigated in various studies in Turkey, no similar study has been found on biodegradation and biosorption of petroleum by Aspergillus parasiticus NRRL:3386 (11)(12)(13). In this context, the study aimed to determine and to compare biodegradation and biosorption capacities of petroleum by different amounts and concentrations of live/dead biomasses and culture supernatants of A. parasiticus NRRL:3386 with gravimetric, Gas Chromatography/Mass Spectrometry (GC/ MS) and Scanning Electron Microscopy analyses (SEM).…”
Section: Introductionmentioning
confidence: 99%